2013
DOI: 10.5588/ijtld.12.0920
|View full text |Cite
|
Sign up to set email alerts
|

Active case finding for tuberculosis among high-risk groups in low-incidence countries [State of the art series. Case finding/screening. Number 3 in the series]

Abstract: In low-incidence countries, tuberculosis (TB) is now largely concentrated in high-risk groups such as migrants, homeless people, illicit drug users, alcoholics and prisoners. This has led to increased efforts to implement targeted active case finding for TB among specific populations. This review examines the evidence supporting active case finding in migrants and social risk groups, as well as the cost-effectiveness of interventions. While data from observational studies support active case finding in defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 66 publications
0
27
0
3
Order By: Relevance
“…This may be explained by differences in migrant groups, migration routes and countries of origin. Other reviews comparing different types of screening (pre-, upon- or post-entry screening) for TB in migrants in low-incidence TB countries report high variations in the yield of screening [37]. This may explain the different conclusions of health economic evaluations regarding the cost-effectiveness of screening for active TB [38].…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by differences in migrant groups, migration routes and countries of origin. Other reviews comparing different types of screening (pre-, upon- or post-entry screening) for TB in migrants in low-incidence TB countries report high variations in the yield of screening [37]. This may explain the different conclusions of health economic evaluations regarding the cost-effectiveness of screening for active TB [38].…”
Section: Discussionmentioning
confidence: 99%
“…An ongoing study to evaluate and optimize tuberculosis control in the Netherlands includes an assessment of the cost–effectiveness of each of the control programme’s components 22 , 23 . Other related investigations have tended to focus on the cost–effectiveness of one specific screening component and/or the detection methods used 24 27 . One review indicated that screening of migrants as they entered a low-incidence country was not very cost-effective and had little impact on overall tuberculosis trends 25 .…”
Section: Discussionmentioning
confidence: 99%
“…No information was available on screening at entry ports for these countries [17]. Zenner et al in a 2013 primary cost effectiveness study identified comparable yields among each screening strategy with at entry screening still not found to be cost-effective and having little impact on overall TB trends [18]. In 2009 and 2014 in the USA, Liu et al and Posey et al, evaluating pre-entry (overseas) screening, identified yields substantially higher than in the UK new entrants screening [19, 20].…”
Section: Discussionmentioning
confidence: 99%